Exploring the Relationship Between Mental Well-Being, Exercise Routines, and the Intake of Image and Performance Enhancing Drugs During the Coronavirus Disease 2019 Pandemic: A Comparison Across Sport Disciplines - Shibata, Mami; Burkauskas, Julius; Dores, Artemisa R.; Kobayashi, Kei; Yoshimura, Sayaka; Simonato, Pierluigi; De Luca, Ilaria; Cicconcelli, Dorotea; Giorgetti, Valentina; Carvalho, Irene P.; Barbosa, Fernando; Monteiro, Cristina; et al. (Frontiers in Psychology, 2021)
Introduction: Physical distancing under COVID-19 pandemic had a significant impact on lifestyles, including exercise routines. While adequate levels of exercise promote mental health, excessive exercise needs more consideration. In this study, we examined the relationship between mental health and addictive behaviors, such as excessive exercise and the use of Image and Performance Enhancement Drugs (IPEDs) across twelve sport disciplines. Materials and Methods: A large cross sectional sample of adult population (N=2,295) was surveyed between April-June 2020 in eight countries. IPEDs use was assessed in conjunction with psychometric measures for problematic exercising (Exercise Addiction Inventory: EAI), appearance anxiety (Appearance Anxiety Index: AAI) and self-compassion (Self-Compassion Scale: SCS). History of addiction, smoking and drinking patterns during physical distancing were also considered. Results were compared across a wide range of sport disciplines, while taking into account the relationship between the psychological measures and IPEDs consumption. Results: The frequency of IPEDs use was higher among the activity group (AG; 34.6%) than the non-activity group (NAG; 14.6%), although AG participants reported less history of addictions (7.1%) than NAG (11.8%). Logistic regression analysis revealed that scores equal to or above cutoff points, in both the EAI and AAI, predicted IPEDs use. As for differences across the various sport disciplines, those practicing Weight Lifting and Cross Fit were found to be more at risk of excessive exercising and more inclined to use a wide range of IPEDs. Almost of those who scored higher in the AAI also showed a high rate of IPEDs use. Conclusions: Although exercise could help to increase wellbeing and prevent addictions during COVID-19 pandemic, our results show that those in the AG are particularly vulnerable to excessive IPEDs use. Sports disciplines associated with higher EAI and AAI scores have also shown higher tendency to excessive IPEDs use. Moreover, over the cut-off scores in EAI or AAI could predict IPEDs consumption regardless of the sport discipline. In light of the current findings, it is necessary to better define the “non-excessive” levels of exercise in various sports disciplines and an adequate intake of IPEDs to ensure safety and wellbeing of people during a pandemic.